State Vocational High School: Educational Investment for the Future in the Mandalika Special Economic Zone - West Nusa Tenggara - Fathurrahman; Samlan; Abdul Haris Khoirul Alam (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This article examines the urgency of establishing a State Vocational Madrasah Aliyah (MAKN) in the Mandalika Special Economic Zone (KEK), West Nusa Tenggara, as a strategic investment in meeting the needs of education and skilled labor in the tourism sector and related industries. The Mandalika KEK, as a super-priority tourism destination, requires competent human resources to support economic growth while still fortifying the